Pathogen-induced pH changes regulate the growth-defense balance in plants - Kesten, Christopher; Gámez-Arjona, Francisco M; Menna, Alexandra; Scholl, Stefan; Dora, Susanne; Huerta, Apolonio Ignacio; Huang, Hsin-Yao; Tintor, Nico; Kinoshita, Toshinori; Rep, Martijn; Krebs, Melanie; Schumacher, Karin; et al. (The EMBO journal, 2019)
Abstract Environmental adaptation of organisms relies on fast perception and response to external signals, which lead to developmental changes. Plant cell growth is strongly dependent on cell wall remodeling. However, little is known about cell wall-related sensing of biotic stimuli and the downstream mechanisms that coordinate growth and defense responses. We generated genetically encoded pH sensors to determine absolute pH changes across the plasma membrane in response to biotic stress. A rapid apoplastic acidification by phosphorylation-based proton pump activation in response to the fungus Fusarium oxysporum immediately reduced cellulose synthesis and cell growth and, furthermore, had a direct influence on the pathogenicity of the fungus. In addition, pH seems to influence cellulose structure. All these effects were dependent on the COMPANION OF CELLULOSE SYNTHASE proteins that are thus at the nexus of plant growth and defense. Hence, our discoveries show a remarkable connection between plant biomass production, immunity, and pH control, and advance our ability to investigate the plant growth-defense balance.
Gesehen am 07.05.2020